Innovation and Supply Chain Management Relationship, Collaboration and Strategies (Cham : Springer International Publishing, 2018)
This book examines key issues, challenges, opportunities and trends in innovation processes and supply chain management. It proposes ways for organizations to improve their performance by developing business strategies, establishing business innovation activities, and aligning business and innovation activities among firms. Further, it showcases and analyzes the implementation of inter- and intra-organizational process improvement activities and the implementation of organizational innovation solutions to address new product and process-related collaborative relationships across the supply chain. The book is useful for researchers, academics and professionals, presenting some of the most advanced research, concepts, and case studies on the relationship between innovation and supply chain.
Part I. Innovation and Supply Chain Management -- Chapter 1. The Intellectual Structure of the Relationship between Innovation and Supply Chain Management -- Part II. The importance of supplier-client relationships -- Chapter 2. Coordination of New Product Development and Supply Chain Management -- Chapter 3. An Investigation of Contextual Influences on Innovation in Complex Projects -- Chapter 4. Necessary Governing Practices for Success and Failure of Client-supplier Innovation Cooperation -- Chapter 5. Collaborative new Product Development in SMEs and Large Industrial Firms. Relationships Upstream and Downstream in the Supply Chain -- Chapter 6. It's Time to Include Suppliers in the Product Innovation Charter (PIC) -- Chapter 7. Mission Impossible: How to Make Early Supplier Involvement Work in New Product Development? -- Part III. Strategies and implications for innovation -- Chapter 8. Purchasing Involvement in Discontinuous Innovation: An Emerging Research Agenda -- Chapter 9. National Culture as an Antecedent for Information Sharing in Supply Chains: A Study of Manufacturing Companies in OECD Countries -- Chapter 10 -- Risk allocation and supplier development in Automotive Supply Chains: A Study of Nissan Europe -- Chapter 11. Does Supply Chain Innovation Pay Off? -- Part IV. Information and Technology -- Chapter 12. Technological Innovations in Supply Chains -- Chapter 13. The Role of Informational and Human Resource Capabilities for Enabling Diffusion of Big Data and Predictive Analytics and Ensuing Performance -- Chapter 14. Adoption of Industry 4.0 Technologies in Supply Chains -- Chapter 15. Advanced Supply Chains: Visibility, Blockchain and Human Behaviour.
Business and Management
text file PDF
Keywords: Management; Industrial management; Business logistics; Engineering economics; Engineering economy; Production management; Industrial organization